Enhancing delamination resistance with intralaminar stiffness tailoring: A numerical study of variable stiffness composites. (1st May 2023) - Liu, Chen-Lin; Li, D.M.; Cheng, Xin
Abstract: In general, strategies and techniques involving intralaminar stiffness tailoring are primarily used to improve compressive capacity (buckling and post-buckling) or tensile properties rather than interlaminate toughness for composites. However, in this work, we show the potential of utilizing intralaminar stiffness tailoring to enhance delamination resistance by specifically investigating the perforated variable stiffness composite plate with a different layout of curvilinear fibers. Firstly, a standard finite element model with the typical cohesive interface to evaluate the delamination performance of different composites is established and is verified against the averrable experimental data of intact constant stiffness composites. Then, two kinds of curvilinear fibers for the perforated composite plates under the Mode I and Mode II delamination test are investigated considering the different fiber layouts and the size of the central cutout. The reaction force–displacement curve and the R-curve of the composites with the curvilinear fibers are obtained to show the enhancement effect of the intralaminar stiffness tailoring on the delamination resistance. The interlaminate toughness of the curvilinear fibers laminate can overperform the straight fibers laminate up to 71% and 63% in the mode Ⅰ and mode Ⅱ cases (r = 8). The underlying mechanism is discussed in detail to inspire new ideas for intra-laminar stiffness tailoring to improve interlaminar toughness.